2024
DOI: 10.1186/s12873-023-00921-8
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ challenges for disaster response: a qualitative study

Jamileh Farokhzadian,
Parvin Mangolian Shahrbabaki,
Hojjat Farahmandnia
et al.

Abstract: Background Healthcare providers, particularly nurses, play a critical role in mitigating the impact of disasters on victims and the healthcare system. However, nurses face unique challenges in disasters that may not experience in their daily practice, which can make it harder for them to deal with disasters efficiently. This study aimed to investigate the challenges faced by nurses for disaster response. Methods A qualitative content analysis appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In a qualitative study, the nursing students noted that they should possess the competencies of managing emotional experiences, implementing strategies to control and prevent infections, and the ability to participate in social anti-epidemic activities during COVID-19 epidemic [ 10 ] Another study showed that the nurses’ competencies of interpersonal relationships and desire to doing research were improved during the COVID-19 outbreak [ 11 ]. Lack of adequate experience and education during biological crises, are the main obstacle for providing effective care [ 12 ]. During COVID-19 pandemic, nurses faced a situation that they had never experienced before in terms of intensity and duration, and their competencies in providing quality care were challenged.…”
Section: Introductionmentioning
confidence: 99%
“…In a qualitative study, the nursing students noted that they should possess the competencies of managing emotional experiences, implementing strategies to control and prevent infections, and the ability to participate in social anti-epidemic activities during COVID-19 epidemic [ 10 ] Another study showed that the nurses’ competencies of interpersonal relationships and desire to doing research were improved during the COVID-19 outbreak [ 11 ]. Lack of adequate experience and education during biological crises, are the main obstacle for providing effective care [ 12 ]. During COVID-19 pandemic, nurses faced a situation that they had never experienced before in terms of intensity and duration, and their competencies in providing quality care were challenged.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses may encounter a range of challenges at the personal, professional, organizational and family levels during disasters. These challenges can have adverse consequences for their well-being [ 7 ]. A Croatian study by Civljak et al, it was found that 70% of nurses reported experiencing physical and psychological injuries during disasters [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evaluations reveal that even experienced nurses exhibit significant deficiencies in disaster management competencies, including gaps in areas such as the incident command system (ICS), ethical triage, epidemiology and surveillance, decontamination procedures, communication during emergencies, and psychological care for disaster victims (Farokhzadian et al, 2024). Addressing these gaps through targeted educational interventions is essential for enhancing the overall preparedness and response capabilities of ENs in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%